Water triggered injectable polylactic acid hydrogel based on zwitterionic sulfobetaine modification for incompressible bleeding and tissue anti-adhesion - Xinran Yang; Xiudan Wang; Lizong Tang; Zhiguang Sun; Xing Gao; Yanmei Zhao; Shike Hou; Jie Shi; Qi Lv (Materials Today Bio)
Massive blood loss is the main cause of prehospital trauma-related death, the development of rapid and effective hemostatic materials is imminent. Injectable hydrogels have the advantages of covering irregular bleeding sites and quickly closing the wound. However, its inherent viscosity can easily precipitate tissue adhesion in vivo and other complications. Based on the anti-protein properties of zwitterion and our previous work about in situ hemostatic/anti-adhesion hydrogel material, we have synthesized a series of injectable hydrogel composed of sulfobetaine-modified polylactic acid (PLA) and gelatin (Gel). These hydrogels could form a smooth film structure by simple water triggering, thereby conferring anti-adhesive properties. We visualized the changes in surface hydrophobicity using fluorescent probes and demonstrated tissue adhesion, rapid hydrophobic interface response, as well as rapid hemostasis for incompressible wounds through in vivo and in vitro experiments. Additionally, we explored the application of hydrogel materials in the scenario of postoperative bleeding, which can effectively prevent unnecessary adhesion through rapid film formation and the anti-protein property of sulfobetaine. We believe that this multifunctional hemostatic hydrogel has the potential to serve as a prehospital emergency treatment of incompressible bleeding and benefit to the postoperative recovery of patients.